Cerebral electrical activity as a tool in evaluating anesthetic effect during balanced anesthesia with sevoflurane - Lorsomradee S. (2014)
The present study was undertaken to provide basic information about bilateral frontal cerebral electrical activity after induction, before and after skin incision, and at a steady state during sevoflurane anesthesia at the end tidal concentration 1, 1.2, 1.4 and 1.6 MAC and determine the association between the electrical cerebral activity with other clinical end points, i.e. motor responses and post-operative recall.